2021
DOI: 10.3390/ijerph182111728
|View full text |Cite
|
Sign up to set email alerts
|

Group-Treatment for Dealing with the Work-Family Conflict for Healthcare Professionals

Abstract: Healthcare professionals’ exposure to work-family conflict negatively affects the health and well-being of the whole family and organizational outcomes. Specified workplace interventions are lacking. Therefore, the aim of the study was to evaluate the feasibility of a two-day group-treatment specifically designed for the needs of healthcare professionals with family responsibilities concerning participation, satisfaction with the intervention and family- and individual-related outcome variables. 24 mostly fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 94 publications
(125 reference statements)
0
1
0
Order By: Relevance
“…Khosravan et al (2018) found that a family-oriented support package, including time management and stress management, reduced WFC among nurses working in Zabol, Iran [ 19 ]. One study found that a group treatment intervention tailored to the needs of healthcare professionals had the potential to improve self-efficacy and work-life balance [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Khosravan et al (2018) found that a family-oriented support package, including time management and stress management, reduced WFC among nurses working in Zabol, Iran [ 19 ]. One study found that a group treatment intervention tailored to the needs of healthcare professionals had the potential to improve self-efficacy and work-life balance [ 20 ].…”
Section: Introductionmentioning
confidence: 99%